CFD SIMULATION OF PRESSURIZATION SYSTEM IN FIRE STAIRS WTC 6 BUILDING - Salahudin Arif; Rita Sundari; Rini Anggraini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Pressurization system in fire stairs is required for high-rise building for safety evacuation in fire attack. This paper has highlighted on the problem of WTC 6 high-rise building with 18 floors related to safety evacuation in fire attack. In real situation, the minimum air pressure (12.5 Pa) at closed condition and minimum air velocity (1 m/s) at open door chamber in fire stairs as stated in the SNI 03-6571-2001 requirements are not fulfilled by the WTC 6 high-rise building. Therefore, a CFD (Computational Fluid Dynamics) simulation has been used to overcome the problems. The CFD results show that volumetric air flow rate of 7.24 m3/s injected to fire stairs in multiple injection system yielded pressure difference of 39.5–44.7 Pa and air velocity of 1.1–1.2 m/s. The CFD simulation implemented in real situation yields air pressure difference of 38.2 Pa in closed condition and air velocity in open door chamber of 1.16 m/s assumed to solve the problem.